Penggunaan batang cuisenaire untuk meningkatkan kemampuan operasi penjumlahan siswa tunagrahita - Dwi Susanti; Ika Noviantari; Herawati Herawati; Hermansyah Hermansyah (Mandalika Mathematics and Educations Journal, 2026)
Students in Grade VIII at Sekolah Luar Biasa (SLB) Negeri Tarakan had difficulty with integer addition operations. To address these difficulties, concrete media such as Cuisenaire rods can be used. Therefore, this research was designed as Classroom Action Research (CAR) aimed at improving integer operation skills through the use of Cuisenaire rods. The CAR was conducted over two cycles, each consisting of planning, action & observation, and reflection. In this study, five students with intellectual disabilities in Grade VIII of SLB Negeri Tarakan were chosen as subjects. Data collection involved observing both teacher and student activities and administering additional skill tests. The results demonstrated progress: in Cycle I, 40% of students achieved learning completeness. Subsequently, there was a 40% increase in Cycle II, bringing the total to 80%, which exceeded the success indicator set at 60%. Furthermore, student activity, which was categorized as fairly active in Cycle I, increased to very active in Cycle II. Similarly, teacher activity improved from good in Cycle I to very good in Cycle II.